HASIL BELAJAR PAI MELALUI METODE COOPERATIVE SCRIPT & MAKE A MATCH DI SMPN 1 SALATIGA - Nurhayati Ekasari (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2020)
This study aims to improve the learning outcomes PAI of Faith in the Angels of God through the Cooperative Script Method and Make a Match in SMP Negeri 1 Salatiga.This research is a Classroom Action Research with stages of planning, implementation, observation, and reflection. Data collection techniques used observation, tests, and documentation. The data obtained in the form of formative test results, practice scores, and observation sheets of learning activities. Then analyzed using individual completeness formulas and classical completeness then drawn conclusions.This is evidenced by the increase in each cycle. In the pre-cycle activities of students who completed as many as 5 students or 26.3% and 14 other students or 73.7% had not been completed. In the first cycle of 9 students or 47.4% and 10 students or 52.6% had not been completed. In cycle II activities there were 17 students or 89.5% and 2 students or 10.5% were not finished.